Cultural Ecofeminism in Pat Mora's Poetry: The Desert as "Curandera" - Khalid, Najwa A. (Al-Adab Journal, 2021)
Eco-feminist writers, in general, investigate the relationship between the oppression of women and the degradation of nature. Cultural ecofeminism, as a branch of ecofeminism, reclaims the twinning of nature with women in terms of productivity and bounty. Cultural eco-feminists emphasize a kind of affinity between elements of nature such as land, woods, desert….etc. and women, in an attempt to reach out to a better cultural community. They try to integrate their views of nature with culture. With such perspective, the current study approaches the poetry of the Mexican American poet, Pat Mora (1942-). Mora's attachment to the Mexican environment and culture greatly influences her literary output which is imbued with images of the desert stressing the cultural concept of the desert as a mother who is endowed with a healing power. She believes that one's culture and environment knit one's heritage and the process of recovering heritage conditions reviving cultural traditions, concepts, practices, values, beliefs and character of place. Thus, her writings focus on the cultural value of land, of communal identities and the Latino mythologies. She depicts Latino people who dwell in a harsh desert from which she unearths the stories of the past to heal the present with special emphasis on the role of land/ desert as a healer by exploiting the image of the curandera, the woman healer in the Mexican culture.